Respuesta :
Answer:
[tex]\displaystyle x=\frac{3 \pm i\sqrt{39}}{4}[/tex]
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Algebra I
- Standard Form: ax² + bx + c = 0
- Factoring
- Quadratic Formula: [tex]\displaystyle x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}[/tex]
Algebra II
- Imaginary Numbers: i = √-1
Step-by-step explanation:
Step 1: Define
2x² - 3x + 6 = 0
Step 2: Solve for x
- [Quadratic] Identify Variables [Standard Form]: a = 2, b = -3, c = 6
- Substitute in variables [Quadratic Formula]: [tex]\displaystyle x=\frac{3 \pm \sqrt{(-3)^2-4(2)(6)}}{2(2)}[/tex]
- [√Radical] Evaluate exponents: [tex]\displaystyle x=\frac{3 \pm \sqrt{9-4(2)(6)}}{2(2)}[/tex]
- [√Radical] Multiply: [tex]\displaystyle x=\frac{3 \pm \sqrt{9-48}}{2(2)}[/tex]
- [√Radical] Subtract: [tex]\displaystyle x=\frac{3 \pm \sqrt{-39}}{2(2)}[/tex]
- Multiply: [tex]\displaystyle x=\frac{3 \pm \sqrt{-39}}{4}[/tex]
- Factor: [tex]\displaystyle x=\frac{3 \pm \sqrt{-1}\sqrt{39}}{4}[/tex]
- Simplify: [tex]\displaystyle x=\frac{3 \pm i\sqrt{39}}{4}[/tex]